Babies Having Babies: Incarcerated Adolescent Parents and Their Emotional Well-Being - Young, Brae (Youth violence and juvenile justice, 2024)
Adolescent parents have been the subject of scrutiny for decades, with a great deal of research focused on how these young parents adjust to their new roles. There is one group of adolescent parents about which we know next to nothing, though: incarcerated adolescent parents. To fill this gap, the current study examines whether parental status affects the emotional well-being (e.g., mental health diagnoses and suicidal tendencies) of incarcerated adolescent parents. We also consider whether these effects are gendered. Results suggest that adolescent parents, especially young mothers, have worsened mental health during incarceration. This effect was most pronounced for suicidal tendencies. These results underscore the importance of providing additional supports for young parents within juvenile facilities. Doing so could not only improve the safety and security of these confinement facilities but improve the long-term outcomes of these young parents and their offspring.